Gel electrolyte precursor, gel composite electrolyte, lithium ion battery and electric equipment

By using polymer monomers, inorganic nanomaterials, initiators and lithium salt solutions, the safety hazards of liquid electrolytes in lithium-ion batteries and the poor mechanical properties of gel electrolytes are solved, and higher mechanical properties and cycle stability are achieved, and the safety and cycle performance of the battery are improved.

CN119798574APending Publication Date: 2025-04-11BYD CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202410377442.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-03-28
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The organic liquid electrolytes used in existing lithium-ion batteries have safety risks, such as flammable and explosive, and the mechanical properties of the gel electrolyte are poor, which affects the durability and reliability of the battery.

Method used

A gel electrolyte precursor is provided, including polymer monomers, inorganic nanomaterials, initiators and lithium salt solutions, through which these components form gel composite electrolytes to improve mechanical properties and cycle stability.

Benefits of technology

It improves the mechanical properties and stability of gel composite electrolytes, reduces the risk of liquid electrolyte leakage, has good thermal stability and safety, and has excellent battery circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004770676370000061
    Figure BDA0004770676370000061
  • Figure BDA0004770676370000071
    Figure BDA0004770676370000071
Patent Text Reader

Abstract

The invention discloses a gel electrolyte precursor, a gel composite electrolyte, a lithium ion battery and electric equipment. The gel electrolyte precursor comprises a polymer monomer, an inorganic nano-material, an initiator and a lithium salt solution, the lithium salt solution comprises a lithium salt and a solvent, and based on the total mass of the gel electrolyte precursor, the content of the inorganic nano-material is 1%-15%. According to the gel electrolyte precursor provided by the invention, the use amount of an electrolyte is reduced, the mechanical property of the electrolyte is improved, and the safety and cycling stability of a battery are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials and relates to a gel electrolyte precursor, a gel composite electrolyte, a lithium ion battery and electrical equipment. Background Art

[0002] Currently, commercial lithium-ion batteries mainly use organic liquid electrolytes, which are widely used in various batteries and energy devices. However, liquid electrolytes also have some disadvantages. For example, the organic solvents in liquid electrolytes are volatile and flammable. Batteries may generate a lot of heat under high temperature, overcharge or over discharge, short circuit, etc., and may cause the electrolyte to burn, causing the battery to burn or even explode, bringing serious safety problems.

[0003] In order to improve the safety performance of batteries, solidifying highly fluid electrolytes is a promising direction, and gel electrolytes have become a viable option to replace liquid electrolytes. However, gel electrolytes also have problems such as poor mechanical properties, which affects the durability and reliability of batteries. Summary of the invention

[0004] Based on this, the present invention provides a gel electrolyte precursor and its application. The gel electrolyte precursor provided by the present invention includes a polymer monomer, an inorganic nanomaterial, an initiator and a lithium salt solution. After forming a gel composite electrolyte, the gel electrolyte precursor improves the mechanical properties and enhances the cycle stability.

[0005] In a first aspect, an embodiment of the present invention provides a gel electrolyte precursor, which includes a polymer monomer, an inorganic nanomaterial, an initiator and a lithium salt solution, wherein the lithium salt solution includes a lithium salt and a solvent, and based on the total mass of the gel electrolyte precursor, the content of the inorganic nanomaterial is 1%-15%.

[0006] In one embodiment, the inorganic nanomaterials include nano-aluminum oxide, nano-silicon dioxide, nano-titanium dioxide, nano-cerium oxide, nano-zinc oxide, nano-zirconium oxide, Li7La3Zr2O 12 , Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 One or more of Zn(GeO4)4.

[0007] In one embodiment, the particle size D50 of the inorganic nanomaterial is 0.2 nm-500 nm.

[0008] In one embodiment, based on the total mass of the gel electrolyte precursor, the content of the polymer monomer is 3%-20%, and the content of the lithium salt solution is 65%-95%.

[0009] In one embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, and lithium bis(trifluoromethane)sulfonyl imide.

[0010] In one embodiment, the solvent includes one or more of ethylene carbonate, p-dimethyl carbonate, ethyl propionate, diethyl carbonate, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, ethyl methyl carbonate, hydrofluoroether, propyl propionate, adiponitrile, fluorobenzene or propylene carbonate.

[0011] In one embodiment, the polymer monomer includes one or more of ethylene glycol diacrylate, triethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,4-butanediol diacrylate, pentaerythritol tetraacrylate, tripropylene glycol diacrylate, decaethylene glycol dimethacrylate, 2-cyanoethyl acrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, di(trimethylolpropane) tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, ethoxylated trimethylolpropane triacrylate, propylene carbonate, ethylene oxide, ethylene glycol diglycidyl ether, acrylic anhydride, and trifluoroethyl methacrylate.

[0012] In one embodiment, the lithium salt solution further includes an additive.

[0013] In one embodiment, the additive includes one or more of vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, vinyl carbonate, propylene sulfite, vinyl sulfate, adiponitrile, succinonitrile, cyclohexylbenzene or dimethyl sulfite.

[0014] The gel electrolyte precursor provided in the first aspect of the present invention includes polymer monomers, inorganic nanomaterials, initiators and lithium salt solution. The polymer monomers and high molecular polymers generated under the action of the initiator form a gel composite electrolyte together with the lithium salt solution and the inorganic nanomaterials, thereby reducing the amount of electrolyte used and improving the stability of the gel composite electrolyte.

[0015] In a second aspect, the present invention further provides a gel composite electrolyte, which is obtained by polymerizing a gel electrolyte precursor.

[0016] In one embodiment, the gel composite electrolyte further comprises: a separator; the gel composite electrolyte is obtained by polymerizing the separator by impregnating a gel electrolyte precursor.

[0017] In one embodiment, the polymerization method is in-situ polymerization.

[0018] The gel composite electrolyte provided in the second aspect of the present invention has higher mechanical properties, and the gel composite electrolyte has good stability in the battery, thereby improving the battery cycle performance.

[0019] In a third aspect, the present invention provides a lithium-ion battery, comprising: a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material and a positive electrode current collector, the positive electrode active material being arranged on the positive electrode current collector, the positive electrode active material comprising at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; and,

[0020] A negative electrode sheet, the negative electrode sheet comprising a negative electrode active material and a negative electrode current collector, the negative electrode active material being disposed on the negative electrode current collector, the negative electrode active material comprising at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metal lithium, and metal lithium composite material; and,

[0021] The gel composite electrolyte of the present invention, the gel composite electrolyte, the positive electrode sheet and the negative electrode sheet are stacked.

[0022] The lithium ion battery provided in the third aspect of the present invention reduces the risk of liquid electrolyte leakage, has good thermal stability and safety, and has excellent battery cycle performance.

[0023] In a fourth aspect, the present invention further provides an electric device, the electric device comprising the lithium-ion battery described in the third aspect. The electric device provided by the embodiment of the present invention comprises the lithium-ion battery described in the second aspect, the lithium-ion battery has a long cycle life and high safety, so that the electric device can be used stably for a long time, which is conducive to improving the performance of the electric device. DETAILED DESCRIPTION

[0024] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] Unless otherwise defined, all technical and scientific terms used in the present invention have the same meaning as those commonly understood by those skilled in the art to which the present invention belongs. The terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used in the present invention includes any and all combinations of one or more of the related listed items.

[0026] Some embodiments of the present invention are described in detail below. In the absence of conflict, the following embodiments and features in the embodiments can be combined with each other.

[0027] In the battery system, the electrolyte is a very important component. It fills the inside of the battery shell, and the positive and negative electrodes and the separator of the battery are immersed in it. The electrolyte has two main functions: first, it provides some active lithium ions to be used as conductive ions during the charging and discharging process. Second, the electrolyte provides ion channels so that lithium ions can move freely in it.

[0028] However, as a substance with extremely low flash point and boiling point in the battery system, the electrolyte is easily ignited. During the use of the battery, the electrolyte often becomes the main cause of safety problems. Therefore, solidifying the electrolyte becomes an effective means to prevent safety hazards.

[0029] Based on this, the present invention provides a gel electrolyte precursor, which includes a polymer monomer, an inorganic nanomaterial, an initiator and a lithium salt solution, wherein the lithium salt solution includes a lithium salt and a solvent, and the content of the inorganic nanomaterial is 1%-15% based on the total mass of the gel electrolyte precursor. The polymer monomer can generate a high molecular polymer under the action of the initiator, and together with the lithium salt solution and the inorganic nanomaterial, a gel composite electrolyte is formed, which reduces the amount of electrolyte and improves the mechanical properties of the gel composite electrolyte. In addition, adding 1%-15% of the total mass of inorganic nanomaterials can reduce the crystallinity of the polymer in the gel electrolyte, which has a good effect on enhancing the ionic conductivity and thermal stability of the electrolyte and preventing thermal runaway of semi-solid lithium ion batteries, and will not cause a decrease in the uniformity and stability of the electrolyte. Optionally, the amount of inorganic nanomaterials can be 1%, 3%, 5%, 7%, 9%, 11%, 13%, 15%.

[0030] In one embodiment, the lithium salt solution further comprises an additive. Optionally, the additive comprises one or more of vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, vinyl carbonate, propylene sulfite, vinyl sulfate, adiponitrile, succinonitrile, cyclohexylbenzene or dimethyl sulfite. Additives play multiple roles in lithium salt solutions. They can improve conductivity, stabilize SEI layer, optimize lithium ion migration, and thus enhance the electrochemical performance of the battery, while improving the energy density of the battery, widening the operating temperature range, and improving the safety of the battery.

[0031] In one embodiment, based on the total mass of the gel electrolyte precursor, the content of the polymer monomer is 3%-20%, and the content of the lithium salt solution is 65%-95%. In the embodiment of the present invention, adding 3%-20% of the total mass of the polymer monomer can make the uniformity and fluidity of the gel electrolyte better. Optionally, the amount of polymer monomer added can be 3%, 5%, 7%, 9%, 11%, 13%, 15%, 17%, 19%. When 65%-95% of the total mass of the lithium salt solution is added, the solvent and the polymer monomer in the lithium salt solution form a gel phase, providing the main ion transmission channel. Optionally, the content of the lithium salt solution can be 65%, 70%, 75%, 80%, 85%, 90%, 95%.

[0032] In one embodiment, the lithium salt includes one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, and lithium bis(trifluoromethane)sulfonyl imide. These lithium salts have high ion conductivity and can effectively transfer lithium ions in the electrolyte, thereby improving the charge and discharge efficiency and performance of the battery. In addition, the above lithium salts generally have good chemical stability within the operating voltage range of the battery, are not easily decomposed or are not easily adversely reacted with other battery components, thereby helping to ensure the long life and safety of the battery.

[0033] In one embodiment, the solvent includes one or more of ethylene carbonate, p-dimethyl carbonate, ethyl propionate, diethyl carbonate, 1-ethyl-(3-dimethylaminopropyl) carbonyl diimide, ethyl methyl carbonate, hydrofluoroether, propyl propionate, adiponitrile, fluorobenzene or propylene carbonate. These solvents can effectively dissolve lithium salts and other additives to form a uniform electrolyte, and can also improve the electrochemical performance of lithium batteries by optimizing the physical and chemical properties of the electrolyte. Specifically, these solvents generally have a higher dielectric constant and a lower viscosity, which helps to enhance the ion conductivity of the electrolyte, thereby improving the charge and discharge efficiency of the lithium battery. At the same time, they also have good chemical stability and thermal stability, which can reduce the side reactions and thermal runaway risks that occur in the battery during operation, and improve the safety and cycle life of the battery. In addition, some solvents also have special properties, such as the introduction of fluorobenzene can improve the antioxidant properties of the electrolyte, and propylene carbonate helps to improve the stability of the SEI layer, so that the lithium battery can operate stably within a wider range of working conditions to meet the needs of various application scenarios.

[0034] In one embodiment, the polymer monomer includes ethylene glycol diacrylate, triethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,4-butanediol diacrylate, pentaerythritol tetraacrylate, tripropylene glycol diacrylate, decaethylene glycol dimethacrylate, 2-cyanoethyl acrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, di(trimethylolpropane) tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, ethoxylated trimethylolpropane triacrylate, propylene carbonate, ethylene oxide, ethylene glycol diglycidyl ether, acrylic anhydride, and trifluoroethyl methacrylate. These polymer monomers generally have good chemical stability and electrochemical stability, and can resist chemical reactions and electrochemical corrosion in the electrolyte, thereby extending the service life of the electrolyte. In addition, their excellent dielectric properties help improve the ion conduction efficiency of the electrolyte and increase the energy density and power density of the battery. At the same time, some polymer monomers also have special functionality. For example, fluorinated polymer monomers can improve the high temperature resistance of the electrolyte, while cyanide-containing polymer monomers can help improve the electrolyte's antioxidant properties. These properties enable gel electrolytes to adapt to a wider range of working conditions and environments, improving the safety and reliability of the battery.

[0035] In one embodiment, the inorganic nanomaterials include nano-aluminum oxide, nano-silicon dioxide, nano-titanium dioxide, nano-cerium oxide, nano-zinc oxide, nano-zirconium oxide, Li7La3Zr2O 12 , Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 Zn(GeO4)4. Inorganic nanomaterials can significantly improve the mechanical properties of gel electrolytes, such as strength and toughness, thereby enhancing the stability of the electrolyte. Specifically, this is because inorganic nanomaterials have high strength and good dispersibility, and can be effectively filled in the electrolyte to form a more stable structure. Secondly, inorganic nanomaterials can interact with polymer chains in gel electrolytes, destroy the regularity of polymer molecular chains, and reduce the crystallinity of polymers, thereby increasing the liquid absorption of electrolytes. The electrolyte can better absorb and retain liquid electrolytes, improve its ionic conductivity, and thus improve the electrochemical performance of the battery. In addition, inorganic nanomaterials such as Li7La3Zr2O 12 , Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14Inorganic ceramic materials such as Zn(GeO4)4 have high ionic conductivity and can significantly increase the ion migration rate in gel electrolytes, thereby improving the overall performance of the battery.

[0036] In one embodiment, the particle size D50 of the inorganic nanomaterial is 0.2-500nm. D50 represents the particle size corresponding to when the cumulative particle size distribution percentage of a sample reaches 50%, also called the median diameter or median particle size. This particle size range makes it easy for the inorganic nanomaterial to disperse and maintain stability in the gel electrolyte, thereby effectively enhancing the mechanical strength and toughness of the electrolyte and improving the safety and durability of the battery. At the same time, the preparation and treatment of inorganic nanomaterials of this particle size are relatively simple and economical, and are suitable for large-scale production. In addition, the appropriate particle size also helps the inorganic nanomaterial to form a good interface compatibility with the gel electrolyte and improve the ion transfer efficiency. Therefore, by adjusting the particle size and doping amount of the inorganic nanomaterial, the performance of the gel electrolyte can be finely controlled to meet the needs of different application scenarios. Optionally, the particle size D50 of the inorganic nanomaterial can be 1nm, 10nm, 30nm, 50nm, 100nm, 200nm, 300nm or 500nm.

[0037] The second aspect of the present invention provides a gel composite electrolyte, which is obtained by polymerizing the above-mentioned gel electrolyte precursor. Optionally, the gel composite electrolyte includes a diaphragm, and the gel composite electrolyte is obtained by polymerizing the above-mentioned gel electrolyte precursor infiltrating the diaphragm. The introduction of the diaphragm further improves the mechanical strength of the gel composite electrolyte, and the preparation process is simple, low-cost, and easy to large-scale and industrialized production. Optionally, the diaphragm includes a polymer such as polyethylene (PE), polypropylene (PP), and one or more of a ceramic material and a nanocomposite material with special properties.

[0038] In one embodiment, the polymerization method of the gel composite electrolyte is in-situ polymerization in the battery. In-situ polymerization can achieve close contact between the electrolyte and the electrode, thereby reducing the interface impedance and improving the ion conduction efficiency of the battery. This close contact also helps to prevent electrolyte leakage and improve the safety of the battery. In addition, in-situ polymerization has good compatibility with existing battery preparation processes and can be easily integrated into existing production lines to reduce production costs. Specifically, the polymerization method of the polymer monomer is not limited, and can be thermally initiated polymerization, photoinitiated polymerization, radiation-induced polymerization, etc. Correspondingly, the initiator is a commonly used thermal initiator, photoinitiator, and radiation initiator. Preferably, thermally initiated polymerization is used in an embodiment of the present invention. Thermally initiated polymerization has significant advantages, and its reaction rate can be flexibly controlled to ensure that the polymerization process is efficiently completed within the required time. At the same time, it is widely applicable to a variety of monomers and exhibits extremely strong versatility. The polymer obtained by thermally initiated polymerization has a stable structure and excellent performance, meeting various application requirements. In addition, the method is simple to operate, does not require complex equipment, and is economical and practical. Specifically, the thermal initiator can be selected from organic peroxides or azo compounds, such as dibenzoyl oxide (BPO), diethylhexyl peroxydicarbonate (EHP), di-tert-butyl peroxide (DTBP), isopropylbenzene peroxide (DCP), azobisisobutyronitrile (AIBN), azobisisoheptanenitrile (ABVN), etc.

[0039] The gel composite electrolyte provided by the present invention has a simple synthesis process for the gel electrolyte and can be directly produced using existing battery production equipment. It also has high ion conductivity, good compatibility with positive and negative electrodes, and can effectively improve the cycle life of lithium batteries.

[0040] The third aspect of the present invention provides a lithium-ion battery, comprising: a positive electrode sheet, the positive electrode sheet comprising a positive electrode active material and a positive electrode current collector, the positive electrode active material is arranged on the positive electrode current collector, the positive electrode active material comprises at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; and, a negative electrode sheet, the negative electrode sheet comprising a negative electrode active material and a negative electrode current collector, the negative electrode active material is arranged on the negative electrode current collector, the negative electrode active material comprises at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metal lithium, and metal lithium composite material; and, the above-mentioned gel composite electrolyte, the gel composite electrolyte, the positive electrode sheet, and the negative electrode sheet are stacked. The lithium-ion battery provided by the present invention has high safety and excellent cycle performance.

[0041] The present invention also provides an electric device, which includes the lithium-ion battery in any of the above embodiments. Specifically, the electric device can be an electric car, an electric motorcycle, an electric bicycle, a mobile power supply, an unmanned aerial vehicle, a mobile phone, a computer, a camera, an electric tool, a smart home or a wearable device. The electric device provided by the present invention includes a lithium-ion battery, which has a long cycle life and good safety, so that the electric device can be used stably for a long time, which is conducive to improving the performance of the electric device.

[0042] The technical solution of the present invention is further illustrated below through specific embodiments and comparative examples.

[0043] Example 1

[0044] (1) Preparation of gel electrolyte precursor

[0045] In an argon atmosphere glove box with a water content of <1ppm and an oxygen content of <1ppm, ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were uniformly mixed at a mass ratio of 3:3:1, and then LiPF6 was added to prepare a lithium salt solution with a LiPF6 concentration of 1mol / L. α-phase nano-alumina (particle size D50 is 30nm), polymer monomer ethylene glycol dimethacrylate EGDMA, and azobisisobutyronitrile AIBN were added to the lithium salt solution, and the mixture was fully stirred to obtain a gel electrolyte precursor. The mass ratio of lithium salt solution, polymer monomer, and nano-alumina in the obtained gel electrolyte precursor was 94:5:1.

[0046] (2) Preparation of positive electrode

[0047] The positive electrode active material lithium iron phosphate (LiFePO4), the conductive agent carbon nanotube (CNT), and the binder polyvinylidene fluoride are mixed in a mass ratio of 95:2:3, and N-methylpyrrolidone (NMP) is added. The mixture is stirred into a uniform positive electrode slurry under the action of a vacuum mixer, and then the positive electrode slurry is evenly coated on both sides of the positive electrode current collector Al foil; after drying at 85°C, it is cold pressed, cut into pieces, and slit, and then dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode sheet.

[0048] (3) Negative electrode preparation

[0049] The negative electrode active material graphite, the conductive agent acetylene black, the binder SBR, and the dispersant CMC are mixed in deionized water at a mass ratio of 93.5:2:2.5:2, and then coated on both sides of the Cu foil for drying, cold pressing, cutting, and slitting to obtain the negative electrode sheet.

[0050] (4) Diaphragm preparation

[0051] The diaphragm is a customized polypropylene diaphragm.

[0052] (5) Preparation of lithium-ion batteries

[0053] The positive electrode sheet, negative electrode sheet and separator are prepared into a battery cell through a Z-shaped stacking machine, and after welding the pole ears and encapsulating with aluminum-plastic film, a soft-pack battery dry cell is obtained. After liquid injection, it is left to stand at room temperature for 24 hours, and then left to stand in an environment of 80°C for 12 hours to form a gel electrolyte in situ. After formation, a lithium-ion battery is obtained.

[0054] Embodiments 2 to 5, Embodiments 10 to 11

[0055] The mass proportion of polymer monomers, inorganic nanomaterials (Al2O3) and mass of Examples 2 to 5 and Examples 10 to 11 are shown in Table 1, and the remaining steps are the same as those of Example 1.

[0056] Embodiments 6 to 9

[0057] Examples 6 to 9: polymer monomer mass ratio, inorganic nanomaterials (Li7La3Zr2O 12 , D50=50nm) and the mass are shown in Table 1, and the remaining steps are the same as in Example 1.

[0058] Comparative Examples 1 to 5

[0059] The mass proportions of the polymer monomers and the inorganic nanomaterial (Al2O3) of Comparative Examples 1 to 5 are shown in Table 1, and the remaining steps are the same as those of Example 1.

[0060] Test method:

[0061] (1) Cycle test

[0062] Take the prepared lithium-ion battery and charge it to 3.65V at 0.5C constant current at room temperature (25±3℃), leave it for 5 minutes, then discharge it to 2.5V at 0.5C constant current, leave it for 5 minutes. This is one cycle. Record the capacity retention rate after 50 cycles at room temperature. The cycle uses a NEWARE test cabinet (model CTE-4080D-5V30A).

[0063] (2) Ionic conductivity test

[0064] Ionic conductivity test, using electrochemical impedance spectroscopy to test the ionic conductivity of gel electrolyte. The test environment is 25°C, the gel electrolyte precursor solution is injected into a steel sheet (thickness D) symmetrical button cell, and the test is performed after in-situ polymerization in the button cell; the impedance R of the electrolyte is tested by an electrochemical workstation, and the frequency range of the impedance test is 10 -2 Hz-10 6Hz, the thickness D between the steel sheets is tested by the thickness gauge, and the ionic conductivity σ of the electrolyte is calculated by the following formula (1). Model of the electrochemical workstation: Solartron1470E.

[0065]

[0066] L: thickness of gel electrolyte, L = D-2d;

[0067] R: volume resistance of gel electrolyte;

[0068] S: area of ​​steel sheet.

[0069] (3) Particle size test

[0070] According to GB / T 41949-2022, the particle sizes of the inorganic nanomaterials in the embodiments and comparative examples were detected using a Mastersizer 3000 laser particle size distribution analyzer.

[0071] Table 1 Gel electrolyte precursor components and battery test results

[0072]

[0073] Through Examples 1-11 and Comparative Examples 1-5, it can be seen that the content of polymer monomers affects the ionic conductivity of the gel composite electrolyte. The polymer content must be within the range described in the present invention to ensure safety performance while ensuring ion transmission performance. At the same time, the addition of nano-alumina described in the present invention improves the ion transmission of the gel electrolyte. This is because the addition of nano-alumina can reduce the crystallinity of the polymer, increase the amorphous region of the polymer, and improve the capacity retention rate during the cycle. However, too much inorganic nanomaterials may agglomerate, which in turn reduces the ionic conductivity of the gel composite electrolyte. On the other hand, too much inorganic nanomaterials will lead to a decrease in the stability of the gel composite electrolyte. Further, when the inorganic filler in the gel composite electrolyte is replaced with Li7La3Zr2O 12 When Li7La3Zr2O 12 It can conduct lithium ions by itself, and provides additional ion transmission channels while polymer ion transmission, thereby significantly improving the ion transmission of gel electrolyte.

[0074] The above is a preferred embodiment of the present application, but it should not be understood as limiting the scope of the present application. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present application, and these improvements and modifications are also considered to be within the scope of protection of the present application.

Claims

1. A gel electrolyte precursor, characterized in that: The gel electrolyte precursor comprises polymer monomers, inorganic nanomaterials, initiators and lithium salt solution, wherein the lithium salt solution comprises lithium salt and solvent. Based on the total mass of the gel electrolyte precursor, the content of the inorganic nanomaterials is 1%-15%.

2. The gel electrolyte precursor according to claim 1, wherein the inorganic nanomaterial comprises nano-aluminum oxide, nano-silicon dioxide, nano-titanium dioxide, nano-cerium oxide, nano-zinc oxide, nano-zirconium oxide, Li7La3Zr2O 12 , Li 3.3 La 0.56 TiO3, LiTi2(PO4)3, Li 14 One or more of Zn(GeO4)4. 3 . The gel electrolyte precursor according to claim 1 , wherein the particle size D50 of the inorganic nanomaterial is 0.2-500 nm.

4. The gel electrolyte precursor according to claim 1, characterized in that: Based on the total mass of the gel electrolyte precursor, the content of the polymer monomer is 3%-20%, and the content of the lithium salt solution is 65%-95%.

5. The gel electrolyte precursor according to claim 1, wherein the lithium salt comprises one or more of lithium hexafluorophosphate, lithium perchlorate, lithium bis(oxalatoborate), lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorophosphate, lithium trifluoromethanesulfonate, and lithium bis(trifluoromethane)sulfonyl imide.

6. The gel electrolyte precursor according to claim 1, wherein the solvent comprises one or more of ethylene carbonate, p-dimethyl carbonate, ethyl propionate, diethyl carbonate, 1-ethyl-(3-dimethylaminopropyl)carbodiimide, ethyl methyl carbonate, hydrofluoroether, propyl propionate, adiponitrile, fluorobenzene or propylene carbonate. 7 . The gel electrolyte precursor according to claim 1 , wherein the lithium salt solution further comprises an additive.

8. The gel electrolyte precursor according to claim 7, wherein the additive comprises one or more of vinyl ethylene carbonate, fluoroethylene carbonate, vinyl sulfite, vinyl carbonate, propylene sulfite, vinyl sulfate, adiponitrile, succinonitrile, cyclohexylbenzene or dimethyl sulfite.

9. The gel electrolyte precursor according to claim 1, wherein the polymer monomer comprises one or more of ethylene glycol diacrylate, triethylene glycol dimethacrylate, trimethylolpropane triacrylate, 1,4-butanediol diacrylate, pentaerythritol tetraacrylate, tripropylene glycol diacrylate, decaethylene glycol dimethacrylate, 2-cyanoethyl acrylate, 1,4-butanediol diacrylate, 1,6-hexanediol diacrylate, trimethylolpropane triacrylate, ethoxylated trimethylolpropane triacrylate, propoxylated trimethylolpropane triacrylate, di(trimethylolpropane) tetraacrylate, ethoxylated pentaerythritol tetraacrylate, dipentaerythritol pentaacrylate, dipentaerythritol hexaacrylate, ethoxylated trimethylolpropane triacrylate, propylene carbonate, ethylene oxide, ethylene glycol diglycidyl ether, acrylic anhydride, and trifluoroethyl methacrylate.

10. A gel composite electrolyte, characterized in that: The gel composite electrolyte is obtained by polymerizing the gel electrolyte precursor according to any one of claims 1 to 9.

11. The gel composite electrolyte according to claim 10, characterized in that: include: Diaphragm; The gel composite electrolyte is obtained by infiltrating the separator with the gel electrolyte precursor according to any one of claims 1 to 9 and polymerizing it.

12. The gel composite electrolyte according to claim 10 or 11, characterized in that: The polymerization method is in-situ polymerization.

13. A lithium ion battery, characterized in that: The invention comprises: a positive electrode sheet, wherein the positive electrode sheet comprises a positive electrode active material and a positive electrode current collector, wherein the positive electrode active material is arranged on the positive electrode current collector, and wherein the positive electrode active material comprises at least one of lithium iron phosphate, lithium iron manganese phosphate, lithium manganate, lithium nickel cobalt manganate, lithium nickel cobalt aluminum oxide, lithium nickel cobalt manganese aluminum oxide, and lithium cobalt oxide; and, A negative electrode sheet, the negative electrode sheet comprising a negative electrode active material and a negative electrode current collector, the negative electrode active material being disposed on the negative electrode current collector, the negative electrode active material comprising at least one of graphite, biomass carbon, lithium titanate, silicon oxide carbon composite material, silicon carbon composite material, metal lithium, and metal lithium composite material; and, The gel composite electrolyte according to any one of claims 10 to 12, wherein the gel composite electrolyte, the positive electrode sheet and the negative electrode sheet are stacked.

14. An electrical device, characterized in that: The electrical equipment comprises the gel composite electrolyte according to any one of claims 10 to 12 or the lithium ion battery according to claim 13.

Citation Information

Cited By

  • Battery monomer and preparation method thereof, battery device, power utilization device and energy storage device

    CN121769227A

  • Preparation method of semi-solid-state battery, battery and device thereof, and power utilization and energy storage device

    CN122068129A